Civic engagement in the community-managed libraries in Oman - Husaini, Mohamed Al (Cybrarians Journal, 2019)
The current study aims to identify the practice of civic engagement in the community-managed libraries in Oman. Community-Managed library is an act of making the library space available for community’s activities, by working in partnership with the voluntary and community sector and other public services. In addition, it is usually involving users as volunteers in the delivery of library services and the organization of activities, that supports and involves the community in various levels of decision making process, work around books and engage in public dialogues and deliberations.A qualitative survey was used to identify the stakeholders’ perception towards the adoption of civic engagement, as a method to develop and sustain these libraries. Stakeholders’ suggestions to overcome the challenges, currently faced by these libraries were also identified. Triangulation method was used to gather information from social media of the libraries beside the open survey. It was discovered that, the six aspects of civic participation are practiced in the community-managed libraries’ and seen in various activities and programs. However, the libraries founders must be motivated through appreciation and support from the government, private sector and other organizations, in order to develop their libraries and keep them sustainable. Finally, the community-managed libraries could model public libraries or serve as extension in the country.
Number: 54
Keywords: Bibliothèques – Oman

أسستها عائلة عمانية: “خزانة العودي” تضم مخطوطات قديمة (صحيفة أثير الإلكترونية, 2019)
أثير - د.محمد بن حمد العريميحرصت العديد من البيوتات والأسر العمانية الكريمة في جناحي القطر العماني (عمان وشرق
Keywords: Bibliothèques – Oman

‏فهرس مخطوطات ‏خزانة ‏الشيخ أحمد بن محمد بن عيسى الحارثي و: 1343هـ - ت: 1422هـ - السعدي, فهد بن علي (ذاكرة عمان, 2019)
Don (Mascate, novembre 2022)
Keywords: Bibliothèques – Oman; Catalogue – Oman; Manuscrits – Oman

‏فهرس مخطوطات ‏خزانة ‏وقف بني سيف - السعدي, فهد بن علي (ذاكرة عمان, 2019)
Don (Mascate, novembre 2022)
Keywords: Bibliothèques – Oman; Catalogue – Oman; Manuscrits – Oman

‏فهرس مخطوطات ‏خزانة ‏وقف بني روح - السعدي, فهد بن علي (ذاكرة عمان, 2019)
Don (Mascate, novembre 2022)
Keywords: Bibliothèques – Oman; Catalogue – Oman; Manuscrits – Oman

من الخزائن التاريخية العمانية خزانة سيف بن سعيد بن خلف الزاملي المعولي - المعولي, أحمد بن حمد بن هلال (الذاكرة, 2019)
Keywords: Bibliothèques – Oman

مكتبة الشيخ محمد بن شامس البطاشي مشروع طموح لتحقيق ونشر تراثه (الذاكرة, 2019)
Keywords: Bibliothèques – Oman

أوائل المطبوعات في خزانة أحمد بن محمد بن عيسى الحارثي قراءة في التقييدات - البرواني, يعقوب بن سعيد (ذاكرة عمان, 2019)
Keywords: Bibliothèques – Oman

مكتبة خزائن الآثار أبرز المشروعات تحقيق ونشر تراث نور الدين السالمي (ذاكرة عمان, 2019)
Keywords: Bibliothèques – Oman; Manuscrits – Oman